Prenatal Origin of Pediatric Leukemia: Lessons From Hematopoietic Development - Cazzola, Anna; Cazzaniga, Giovanni; Biondi, Andrea; Meneveri, Raffaella; Brunelli, Silvia; Azzoni, Emanuele (Frontiers in Cell and Developmental Biology, 2021)
Several lines of evidence suggest that childhood leukemia, the most common cancer in young age, originates during in utero development. However, our knowledge of the cellular origin of this large and heterogeneous group of malignancies is still incomplete. The identification and characterization of their cell of origin is of crucial importance in order to define the processes that initiate and sustain disease progression, to refine faithful animal models and to identify novel therapeutic approaches. During embryogenesis, hematopoiesis takes place at different anatomical sites in sequential waves, and occurs in both a hematopoietic stem cell (HSC)-dependent and a HSC-independent fashion. Despite the recently described relevance and complexity of HSC-independent hematopoiesis, few studies have so far investigated its potential involvement in leukemogenesis. Here, we review the current knowledge on prenatal origin of leukemias in the context of recent insights in developmental hematopoiesis.